2016
DOI: 10.1155/2016/9291713
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training in Parkinson’s Disease: A Review of Studies from 2000 to 2014

Abstract: Cognitive deficits are prevalent among patients with Parkinson's disease (PD), in both early and late stages of the disease. These deficits are associated with lower quality of life, loss of independence, and institutionalization. To date, there is no effective pharmacological treatment for the range of cognitive impairments presented in PD. Cognitive training (CT) has been explored as an alternative approach to remediating cognition in PD. In this review we present a detailed summary of 13 studies of CT that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 105 publications
0
21
0
1
Order By: Relevance
“…Recent studies have also shown that PD complicated by cognitive dysfunction confers a shorter life expectance compared to PD with normal cognitive function [52]. The demand for nonpharmacological interventions is increasing and there is, although modest, growing evidence of the benefit of cognitive interventions in PD [20][21][22]24]. While some studies have shown the efficacy of cognitive interventions in persons with PD, studies on newly diagnosed patients, excluding those with severe cognitive decline, are sparse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have also shown that PD complicated by cognitive dysfunction confers a shorter life expectance compared to PD with normal cognitive function [52]. The demand for nonpharmacological interventions is increasing and there is, although modest, growing evidence of the benefit of cognitive interventions in PD [20][21][22]24]. While some studies have shown the efficacy of cognitive interventions in persons with PD, studies on newly diagnosed patients, excluding those with severe cognitive decline, are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…This patient group is already burdened by polypharmacy and therefore investigating nonpharmacological treatment options is crucial [19]. Recent systematic reviews on cognitive training in PD have shown evidence of improvements in overall cognition as well as in working memory, processing speed, and executive functions [20][21][22][23][24]. Most studies have had a broad cognitive approach [25][26][27] making it hard to know what aspects of training that is causing the improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the inconsistencies in the training interventions and outcome measures, the authors emphasized on conducting large, well-designed studies in future. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Among these disorders, the incidence rate of PD is second in the world and achieves to 1%–2% in the people over 60 years old (Burke & O'Malley, ; Mullard, ; Shen & Ji, ). As the major neurological characteristics of PD, the dopaminergic neurons in the substantia nigra pars compacta is progressive degenerative (Glizer & MacDonald, ), which is accompanied by the appearance of α‐synuclein inclusions called Lewy bodies (Zhang, An, Zhang, & Pu, ). In the pathogenesis of PD, rest tremors, rigidity, bradykinesia, and postural abnormalities are be diagnosed as main symptoms of PD in clinic.…”
Section: Introductionmentioning
confidence: 99%